2014
DOI: 10.1124/jpet.113.211706
|View full text |Cite
|
Sign up to set email alerts
|

Activation ofα4β2*/α6β2* Nicotinic Receptors Alleviates Anxiety during Nicotine Withdrawal Without Upregulating Nicotinic Receptors

Abstract: Although nicotine mediates its effects through several nicotinic acetylcholine receptor (nAChR) subtypes, it remains to be determined which nAChR subtypes directly mediate heightened anxiety during withdrawal. Relative success in abstinence has been found with the nAChR partial agonist varenicline (Chantix; Pfizer, Groton, CT ); however, treatment with this drug fails to alleviate anxiety in individuals during nicotine withdrawal. Therefore, it is hypothesized that success can be found by the repurposing of ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 45 publications
3
27
0
Order By: Relevance
“…In contrast, an anxiogenic effect of withdrawal at 24 hours is observed as an increased latency to consume a palatable food in a novel environment when compared to nicotine-treated mice. [28][29][30][31]58 The increased time observed in the BDNF Met/Met mice to initially approach and eat the palatable food during training for the NIH test ( Figure 1B) might be indicative of either increased anxietylike behavior as the food is a novel object introduced into the home cage, or it could be revealing a deficit in training behavior as studies have shown that the BDNF Met/Met mice exhibit impaired spatial and working memory. 59 However, no significant differences between genotype or between treatment groups by the end of training were observed, suggesting that although acquisition of the task was slow, it did not affect the overall performance of these mice on home or novel day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, an anxiogenic effect of withdrawal at 24 hours is observed as an increased latency to consume a palatable food in a novel environment when compared to nicotine-treated mice. [28][29][30][31]58 The increased time observed in the BDNF Met/Met mice to initially approach and eat the palatable food during training for the NIH test ( Figure 1B) might be indicative of either increased anxietylike behavior as the food is a novel object introduced into the home cage, or it could be revealing a deficit in training behavior as studies have shown that the BDNF Met/Met mice exhibit impaired spatial and working memory. 59 However, no significant differences between genotype or between treatment groups by the end of training were observed, suggesting that although acquisition of the task was slow, it did not affect the overall performance of these mice on home or novel day.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] In particular, studies have shown an anxiolytic effect of chronic nicotine as measured by a decreased latency to consume a palatable food in a novel environment when compared to saline-treated mice. In contrast, an anxiogenic effect of withdrawal at 24 hours is observed as an increased latency to consume a palatable food in a novel environment when compared to nicotine-treated mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the effects of nicotine on fear conditioning, there is evidence that β2-containing nAChRs mediate nicotine’s effects on anxiety. For example, an α4β2 nAChR agonist, ABT-418, was found to increase open arm time in the EPM and both ABT-418 and an α4β2 nAChR partial agonist, ABT-089, reversed the anxiogenic effects of nicotine withdrawal (Brioni et al, 1994; Decker et al, 1994; Yohn, Turner, & Blendy, 2014). Brioni et al (1994) also showed that the anxiolytic effects of ABT-418 were reversed by the nAChR antagonist mecamylamine, which suggests that sustained nAChR activity is required for the anxiolytic effect of ABT-418.…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disordersmentioning
confidence: 99%
“…Also, Paylor et al (1998) showed that α7 nAChR-lacking KO mice show decreased levels of anxiety in the EPM paradigm, while an α7-selective agonist, PNU-282987, was shown to increase anxiety in the OF paradigm (Pandya & Yakel, 2013). Similarly, desensitization of α7 nAChRs by using an α7 partial agonist, ABT-107, was found to reverse the anxiogenic effects of nicotine withdrawal (Yohn et al, 2014). Overall, these results suggest that in animals, nicotine has differential effects on anxiety in different strains/species and anxiety-related animal models.…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disordersmentioning
confidence: 99%